Does Preoperative Atrial Fibrillation Portend a Poorer Prognosis in Patients Undergoing Isolated Aortic Valve Replacement? A Multicentre Australian Study - Saxena, A.; Dinh, D.; Reid, Christopher; Smith, J.; Shardey, G.; Newcomb, A. (2013)
Background: Preoperative atrial fibrillation (preop-AF) has been associated with poorer early and late outcomes after cardiac surgery. Few studies, however, have evaluated the impact of preop-AF on early and late outcomes after isolated aortic valve replacement (AVR). Methods: Data obtained prospectively between June 2001 and December 2009 by the Australian and New Zealand Society of Cardiac and Thoracic Surgeons National Cardiac Surgery Database Program was retrospectively analyzed. Patients who underwent concomitant atrial arrhythmia surgery/ablation were excluded. Demographic and operative data were compared between patients undergoing isolated AVR who presented with preop-AF and those in sinus rhythm. The independent effect of preop-AF on 12 short-term complications and long-term survival was determined using binary logistic and cox regression, respectively. Results: Isolated AVR surgery was performed in 2789 patients; 380 (13.6%) presented with preop-AF. Preop-AF patients were generally older (mean age, 73 vs 68 years; P < 0.001) and presented more often with comorbidities including congestive heart failure, diabetes, and cerebrovascular disease (all P < 0.05). There was a trend toward increased 30-day mortality in patients with preop-AF on multivariate analysis (P = 0.051). The incidence of early complications was similar in both groups on multivariate analysis (P > 0.05). Preop-AF was independently associated with reduced long-term survival (hazard ratio, 1.36; 95% confidence interval, 1.01-1.83; P = 0.041). Conclusions: Preop-AF is associated with an increased risk of late mortality after isolated AVR. As such, concomitant atrial ablation with AVR should be prospectively studied.